Some features of the meaning “literary text” in the pragmalinguistic aspect - Akkuzova, Ainur; Mankeyeva, Zhamal; Raushan Baiymbetova., Abdyzhalil Akkuzov, Ulbossyn Kaiyrbekova, (Opción, 2019)
In this research, it is defined that in the world scientific linguistic literature until this time the main concept is “language processes are connected with thinking, mentality processes” and it is proved that a language of fiction should be considered from the point of national character that transmits by words. Through the scientific views and opinions in the article, especially the main: to characterize a word as a means that delivers a national culture and ethnic features gives an opportunity to define the peculiarities of readers’ perception